APPLICATION OF GIS FOR ASSESSING PRAWN FARM DEVELOPMENT IN TULLY-CARDWELL, NORTH QUEENSLAND - Zainul Hidayah (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2011)
In recent years, Geographical Information Systems (GIS) has been employed for various studies in aquaculture where geographical factors, natural resources and human activities are involved. With an adequate database GIS, can serve as powerful tools in aquaculture. GIS have capabilities of organizing, analyzing, and displaying large, spatially explicit datasets due to spatial nature of the factors involved in aquaculture development particularly for site suitability studies. This study is intended to become a preliminary investigation for the development of prawn farm in Tully-Cardwell region of North Queensland. The aim of this research is to identify suitable sites for development of prawn farming using GIS multi-based criteria based on the basic requirements for prawn farming, for instance: suitable elevation and slope, proximity to water and distance from urban areas. Key words: Geographical Information Systems (GIS), Tully Cardwell, North Queensland, Prawn farm